Perceptions of positive attitudes toward people with spinal cord injury : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in psychology at Massey University - Lys, Kathy Jane (Massey University, 1994)
The aim of the present study was to identify differences in perceptions of positive attitudes toward persons with SCI (spinal cord injury). The four groups surveyed included 35 people with SCI, 27 rehabilitation workers from a spinal injuries rehabilitation unit in Auckland, 16 rehabilitation workers from a hospital rehabilitation unit in Palmerston North, and 37 people from the general population. Participants completed the Modified Issues in Disability Scale-Transitional Version (Makas, 1993), adjusted slightly for the purpose of the study. The people with SCI were considered the judges of what a positive attitude consisted of, and scored higher on the measure than all other groups. The results showed that the Auckland rehabilitation workers and the general population group differed significantly from the people with SCI in their perceptions of positive attitudes, whereas the Palmerston North rehabilitation workers did not. Age and ethnic identity were significantly related to perceptions of attitudes, with younger adults and Europeans being more aware of positive attitudes than older adults and non-Europeans. Professionally trained rehabilitation workers had a greater awareness than inservice trained workers of what constituted a positive attitude toward people with SCI. The results indicated a lack of awareness among rehabilitation workers and the general population about what constitutes a positive attitude toward people with SCI. Recommendations for future research and practical suggestions for improving awareness were made.
Keywords: Spinal cord -- Wounds and injuries; Psychological aspects; Attitudes (Psychology); Discrimination against people with disabilities